Neonatal procedural pain affects state, but not trait anxiety behavior in adult rats. Issue 8 (16th November 2021) - de Kort, Anne R; Joosten, Elbert A; Patijn, Jacob; Tibboel, Dick; van den Hoogen, Nynke J
Abstract: The influence of neonatal experiences upon later‐life affective behavior is increasingly recognized, but the reported effects on anxiety are often contradictory. The observed effect may depend upon the type of anxiety (state or trait) affected. The current study aims to investigate whether neonatal repetitive needle pricking alters anxiety behavior in adulthood, by assessing both state and trait anxiety in rats. Sprague–Dawley rat pups received four unilateral needle pricks per day, while controls received four tactile stimuli or were left completely undisturbed during the first postnatal week. Mechanical sensitivity was assessed in the neonatal phase and throughout the development. State anxiety was assessed in the open field test and trait anxiety in the elevated zero maze. The results show that repetitive needle pricking leads to acute mechanical hypersensitivity, but does not affect baseline mechanical sensitivity throughout development. In adulthood, animals previously exposed to neonatal procedural pain (including repetitive handling and removal from litter) showed lower state anxiety but did not differ in trait anxiety, as compared with the undisturbed controls. These findings indicate that early‐life procedural pain decreases state but not trait anxiety behavior in later life in a rodent model of repetitive needle pricking.